Karakteristik Elemen Sistem Pariwisata Ekowisata Desa Wisata Nglanggeran dan Wisata Desa pada Desa Wisata Pentingsari - Purbasari, Novia; Manaf, Asnawi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Tourism Village was chosen as an alternative to the development of tourism in Yogyakarta, this is because the Tourism Village closer to the people so as to involve the community as a component of the main actors. Many developed Tourism Village in Yogyakarta, has brought new challenges being able to package the elements of the tourism system to compete with the characteristics possessed by Tourism Village itself. Tourism Village Nglanggeran a successful ecotourism in conservation efforts, while the Tourism Village is a rural tourist Pentingsari successful in empowering local communities. Departing from this success, comes the following questions: How does the system elements on ecotourism Tourism Village tourism and rural tourism in Nglanggeran Pentingsari Tourism Village? This research aims to identify the characteristics of element tourism system in Nglanggeran and Pentingsari Tourism Village. The analysis technique used is descriptive analysis. To answer the research question to identify elements of the tourism system followed by comparing the characteristics of the elements of the system at both the tourist village. The results obtained from this research are attractions and visitor are best element that describes the characteristics of the both Tourism Village. The main attraction in Nglanggeran ecotourism Village is conservation action that attract the wanderlusters and â€œpecinta alamâ€. While in Pentingsari rural tourism village, the rural live of society become the main attraction for educational tourism that attract the student to live in program in Pentingsari rurl tourism village.